TRANSITIVITY SYSTEM ON BUILDING CHARACTER OF MR. SUMMERS IN THE LOTTERY BY SHIRLEY JACKSON - Nugraha, Intan Siti; Mahdi, Sutiono (Celtic: A Journal of Culture, English Language Teaching, Literature and Linguistics, 2020)
Â The Lottery is one of the most famous American canonicals written by Shirley Jackson (1948) which is sensational. The theme brought triggers controversy to contemporary critics. The story exposed one of the darkest dualities of human nature in â€˜the lotteryâ€™ carried out by the society in the story. The controversial character in the Lottery which evokes social culture issue is analyzed by investigating the process types related to the character. Types of process are essential in the building characters or characterization. Thus, this study analyzed the main character of a literary work â€œThe Lotteryâ€ by Shirley Jackson (1948) using transitivity system of Systemic Functional Linguistic (SFL) approach. The data were all clauses related to Mr. Summers as the main character in this short story. They were analyzed using concept of transitivity system. The result shows that the author of the short story dominantly uses verbal process to construct the main character through his verbiage which is 52.63% of the total processes in clauses. In addition material process which also occupies high number (32.90%) after verbal process denotes that the character does activities in the domestic and physical domain. The relational process (7.89%) is used to characterize the characters explicitly. The mental process (5.26%) is used to depict the charactersâ€™ cognition while behavioural process (1.32%) is employed to a common activity.